Adaptability and pathogenicity of monosporascus species in cucurbits - Cavalcante, Allinny Luzia Alves (Universidade Federal Rural do Semi-Árido, 2021)
In this study, five new recently described Monosporascus species, M. brasiliensis, M. caatinguensis, M. mossoroensis, M. nordestinus and M. semiaridus, which were found on weeds collected from cucurbits cultivation fields in northeastern Brazil, were characterized regarding in vitro mycelial growth at different pH levels and salinity (NaCl) concentrations, their pathogenicity to selected species of melon, watermelon, cucumber and pumpkin, and their in vitro sensitivity to the fungicides boscalid, carbendazim, cyprodinil, fluazinam, and fludioxonil. The results revealed great variability among the representative isolates of each Monosporascus species. All of them showed a wide range of tolerance to different pH levels, with the OpH of the species ranging from 5.72 to 8.05. NaCl concentrations significantly reduced in vitro mycelial growth, with EC50 above 900 mM for all species, although no concentration was able to inhibit them completely. In pathogenicity tests, all the cucurbits evaluated, were susceptible to the five Monosporascus species in a greenhouse experiment using artificial inoculation of roots. Moreover, all Monosporascus species were highly susceptible to the fungicides fludioxonil and fluazinam, exhibiting EC50 values below 1 mg/L a.i. Our results provide relevant information about the response of these new Monosporascus species to environmental factors, plant genotypes and fungicides
Keywords: Crescimento micelial; Fungicidas; Fungos radiculares; Patogenicidade; pH; Salinidade; Virulência; Fungicides; Mycelial growth; Pathogenicity; pH; Salinity; Soilborne fungi; Virulence; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA